Proceedings of the Ocean Drilling Program, 153 Scientific Results 1997
DOI: 10.2973/odp.proc.sr.153.034.1997
|View full text |Cite
|
Sign up to set email alerts
|

Data report: oxides, sulfides, and associated phases in veins and hydrothermally altered peridotitic rocks

Abstract: The ductile to brittle deformation and the associated hydrothermal mineralogical record in Holes 920B and 920D peridotites are complex. Remnants of a high-temperature phase (brown hornblende, talc) are preserved in the seΦentinized harzburgites. Primary chromites in the harzburgite are altered to ferritchromite. Magnetite, which originated from olivine breakdown during seΦβntinization, (1) recrystallizes, mimicking mesh and ribbon textures, and (2) reorganizes in veins and trails. Primary sulfide minerals rare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 5 publications
1
9
0
Order By: Relevance
“…These compositions are similar to those observed in serpentinized peridotites (e.g. ODP leg 920B; Gaggero & Cortesogno, 1997b).…”
Section: Ca-al Silicatessupporting
confidence: 83%
“…These compositions are similar to those observed in serpentinized peridotites (e.g. ODP leg 920B; Gaggero & Cortesogno, 1997b).…”
Section: Ca-al Silicatessupporting
confidence: 83%
“…On the deepest parts, the mineralogical zonation from barren serpentinite to Fe‐Ca‐silicates to semi‐massive sulphides and then to Cu‐rich MS (Figures e and b) has never been reported before this study. The ilvaite‐andradite‐diopside assemblage has been described in low‐grade metamorphic serpentinites (Agata & Agachi, ) and in oceanic ultramafic settings (Gaggero, Cortesogno, & Gazzoti, ). Gaggero et al () suggested that this assemblage precipitated from early serpentinization‐derived fluids.…”
Section: Discussionmentioning
confidence: 99%
“…The ilvaite‐andradite‐diopside assemblage has been described in low‐grade metamorphic serpentinites (Agata & Agachi, ) and in oceanic ultramafic settings (Gaggero, Cortesogno, & Gazzoti, ). Gaggero et al () suggested that this assemblage precipitated from early serpentinization‐derived fluids. Gustafson () showed that the ilvaite‐hedenbergite‐andradite‐magnetite assemblage is stable at low f O2 (10 –25 to 10 –32 ), high‐T (425 ± 75°C) conditions without strong changes if considering diopside instead of hedenbergite.…”
Section: Discussionmentioning
confidence: 99%
“…All serpentine analyses, except those of V4 veins, also contain significant amounts of sulfur, probably located in sulfide micrograins disseminated both in serpentine and among magnetite grains in veins [ Gaggero et al , 1997; Alt and Shanks , 2003]. The high sulfur content of MARK serpentinites has already been noted by Alt and Shanks [2003], which they explain by invoking an earlier phase of fluid circulation through grabbros before percolating through ultramafic units.…”
Section: Vein Chemistrymentioning
confidence: 99%